Pipelle Endometrial Sampling Versus Conventional Dilatation & Curettage in Patients With Abnormal Uterine Bleeding - Sarosh, Muntiha; Ghafoor, Faiza; Shakoor, Shumaila (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the efficacy of endometrial sampling using Pipelle compared with Conventional dilatation & curettage in women with bleeding from the uterus that is heavier/longer than usual or that occurs at an irregular time. Place and duration of study: Department of Obs & Gynae, Aviceena Medical College/Hospital from June 2020 to June 2021. Methodology: This comparative study was carried out in 57 women with abnormal uterine bleeding. Endometrial sampling was done by Pipelle without cervical dilatation followed by dilatation & curettage. Histopathology results were compared. Histopathological evaluation of the samples obtained by Dilatation & curettage was considered gold standard. Results: All endometrial tissue samples (100%) collected by dilatation & curettage while 98% obtained by the Pipelle sampler were acceptable for histopathology. Histopathological investigation of 57 samples acquired through dilatation & curettage confirmed proliferative and Secretory changes, Endometrial Hyperplasia, Endometritis in 15,13, 19, and 4 subjects while Endometrial Polyps and Malignant change in 2 and 4 specimens respectively. Conclusion: Pipelle endometrial sampling is an efficient outpatient procedure thus avoiding hazards of general anesthesia with a great precision for evaluating benign and malignant endometrial pathology.